Chemoresistance and Cancer-Related Inflammation: Two Hallmarks of Cancer Connected by an Atypical Link, PKCζ - Rimessi, Alessandro; Patergnani, Simone; Ioannidi, Elli; Pinton, Paolo (Frontiers in Oncology, 2013)
Atypical protein kinase C isoforms are serine threonine kinases involved in various pathological conditions. In recent years, the PKCζ isoform has emerged as an important regulator of multiple cellular processes operating in cancer. In this review, we will focus on the PKCζ isoform as an oxidative-sensing kinase involved in cancer-related inflammation and chemoresistance. We will discuss its nuclear localization and its possible pivotal role in connecting inflammation with drug resistance.